A Mesocrystal‐Like Morphology Formed by Classical Polymer‐Mediated Crystal Growth. (4th September 2017) - Smeets, Paul J. M.; Cho, Kang Rae; Sommerdijk, Nico A. J. M.; De Yoreo, James J.
Abstract: Growth by oriented assembly of nanoparticles is a widely reported phenomenon for many crystal systems. While often deduced through morphological analyses, direct evidence for this assembly behavior is limited and, in the calcium carbonate (CaCO3 ) system, has recently been disputed. However, in the absence of a particle‐based pathway, the mechanism responsible for the creation of the striking morphologies that appear to consist of subparticles is unclear. Therefore, in situ atomic force microscopy is used to investigate the growth of calcite crystals in solutions containing a polymer additive known for its ability to generate crystal morphologies associated with mesocrystal formation. It is shown that classical growth processes that begin with impurity pinning of atomic steps, leading to stabilization of new step directions, creation of pseudo‐facets, and extreme surface roughening, can produce a microscale morphology previously attributed to nonclassical processes of crystal growth by particle assembly. Abstract : The first mechanistic picture is presented of the process by which crystals develop exotic morphologies previously attributed to "mesocrystals." The canonical mesocrystal of calcite grown in polystyrene sulfonate solution forms through completely classical processes of step advancement on faceted crystal surfaces, putting to rest the notion that a typical mesocrystal morphology is evidence for a growth pathway via particle assembly.